2018
DOI: 10.14195/2182-8830_6-1_7
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Narrative Design beyond the Secret Art Status: A Method to Verify Design Conventions for Interactive Narrative

Abstract: In recent years, game narrative has emerged as an area for novel game concepts and as a strategy to distinguish a particular title. However, innovation in this area comes primarily from indie companies and individual efforts by noted designers. There is a lack of trained specialists ready to produce interactive narrative experiences. Many existing practitioners are self-trained and often rely on intuition in their design practice. A key element missing from the effort towards a more sustained development and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…As the results show video games are able to evoke such strong emotional states and, probably, adventure games and role-playing games might be especially suited for this type of emotional involvement (e.g., Arbeau et al, 2020;Butt & Dunne, 2019;Dechering & Bakkes, 2018;Koenitz et al, 2018; see S. L. Bowman & Lieberoth, 2018). For some players, sadness evoked by the game is experienced as a reward, an appreciation of a thought-provoking experience (Bopp et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…As the results show video games are able to evoke such strong emotional states and, probably, adventure games and role-playing games might be especially suited for this type of emotional involvement (e.g., Arbeau et al, 2020;Butt & Dunne, 2019;Dechering & Bakkes, 2018;Koenitz et al, 2018; see S. L. Bowman & Lieberoth, 2018). For some players, sadness evoked by the game is experienced as a reward, an appreciation of a thought-provoking experience (Bopp et al, 2016).…”
Section: Discussionmentioning
confidence: 88%
“…Given the status of IND research as an interdisciplinary field of study, the questions of adequate frameworks (Koenitz and Eladhari, 2019;Koenitz, 2021), design conventions (Murray, 2011;Koenitz et al, 2018a), transhistorical approaches (Rouse and Holloway-Attaway, 2020;Holloway-Attaway and Rouse, 2022) and evaluation (Roth, 2016;Steinemann et al, 2017) are ongoing concerns. Lately, the question of ethics in the creation process (Fisher and Schoemann, 2018;Barbara et al, 2021) and of decolonialization of underlying narrative structures and other assumptions (Koenitz et al, 2018b;Silva et al, 2022) have found increased attention in part inspired by similar developments in game studies (Mukherjee, 2018;de Paula, 2021;Trammell, 2022).…”
mentioning
confidence: 99%